Socioemotional wealth and culture in family businesses: A scientometric analysis - Lopez-Espitia, Yurani; Vivares, Jorge A; Ramirez-Ospina, Duvan Emilio (International Journal of Innovative Research and Scientific Studies, 2025)
Socioemotional wealth and culture have emerged as relevant topics of study for their contribution to the understanding of family businesses, which has generated an important flow of knowledge in a short period of time. However, no study was found in the literature to understand, in a generic way, the dynamics of the existing scientific production. Thus, the objective of this article is to perform a scientometric mapping of socioemotional wealth and culture based on a query in Web of Science and Scopus. The data were analyzed under two perspectives: the first, a scientometric analysis, and the second, using Tree of Science to identify thematic trends. The results show a growth from 2001 to 2023 of 17.39%, and the country with the highest production, impact, and quality of articles is the United States. Two thematic trends linking socioemotional wealth with culture were also identified: 1) social perspectives in family business research, and 2) ethics and strategic management in family businesses. Overall, the results of this study are important for researchers who wish to contribute to this topic and to have a global perspective of its academic dynamics in order to understand more and more the heterogeneity of family businesses.